Magnetic Shielding, Aromaticity, Antiaromaticity and Bonding in the Low‐Lying Electronic States of S2N2. Issue 63 (8th November 2018) - Karadakov, Peter B.; Al‐Yassiri, Muntadar A. H.; Cooper, David L.
Abstract: Aromaticity, antiaromaticity and chemical bonding in the ground (S0 ), first singlet excited (S1 ) and lowest triplet (T1 ) electronic states of disulfur dinitride, S2 N2, were investigated by analysing the isotropic magnetic shielding, σ iso (r ), in the space surrounding the molecule for each electronic state. The σ iso (r ) values were calculated by state‐optimized CASSCF/cc‐pVTZ wave functions with 22 electrons in 16 orbitals constructed from gauge‐including atomic orbitals (GIAOs). The S1 and T1 electronic states were confirmed as 1 1 Au and 1 3 B3u, respectively, through linear response CC3/aug‐cc‐pVTZ calculations of the vertical excitation energies for eight singlet (S1 –S8 ) and eight triplet (T1 –T8 ) electronic states. The aromaticities of S0, S1 and T1 were also assessed using additional magnetic criteria including nucleus‐independent chemical shifts (NICS) and magnetic susceptibilities calculated at several levels of theory, the highest of which were CCSDT‐GIAO/cc‐pVTZ for S0 and CASSCF(22, 16)‐GIAO/aug‐cc‐pVQZ for S1 and T1 . The results strongly suggest that: 1) the S0 electronic ground state of S2 N2 is aromatic but less so than the electronic ground state of benzene; 2) S1 is profoundly antiaromatic, to an extent that removes any bonding interactions that would keep the atoms together; and 3) T1 is also antiaromatic, but its antiaromaticity is more moderate and similar to that observed in the electronic ground state of square cyclobutadiene. S2 N2 is the first example of an inorganic ring for which theory predicts substantial changes in aromaticity upon vertical transition from the ground state to the first singlet excited or lowest triplet electronic states. Abstract : Is S2 N2 aromatic? Off‐nucleus shielding calculations strongly suggest that S2 N2 is the first example of an inorganic ring showing substantial changes in aromaticity upon transition from the ground state (aromatic but less so than benzene) to the first singlet excited (strongly antiaromatic and unstable) or lowest triplet (antiaromatic) electronic states (see figure).